Beyond the Theory: Symbolic Interactionism and EAP Practitioners' Professional Identity Construction - Afna, Mauloeddin (JADEs Journal of Academia in English Education, 2023)
This article examined the construction of professional identity among TESOL graduate students who are preparing to teach English. The study investigated the meanings that these students associate with professionalism and the challenges they encounter in the English for Academic Purposes (EAP) profession. Even though the EAP field has received significant research attention, few studies have focused on the construction of professional identity among practitioners themselves. This research employs in-depth interviews with 7 alumni of the English Education Department at IAIN Langsa, Kota Langsa to comprehend how EAP practitioners develop their professional identity. The study utilizes key theories from Symbolic Interactionism to create a theoretical framework on EAP identity. The study's results demonstrate that EAP practitioners perceive themselves as effective teachers, but they encounter tensions around positioning, marginalization, and recognition. These tensions often create fragmented identities that may correspond to academic or support service roles. The study emphasizes the need for a shared understanding of EAP practitioner identity to decrease professional disarticulation